(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abstract: Artificial Intelligence (AI) has rapidly emerged as a transformative force in strategic decision-making across various industries. This paper provides a comprehensive analysis of AI-driven management practices, focusing on the integration of AI technologies into organizational decision-making processes. Through the examination of theoretical frameworks, case studies, and practical applications, the paper explores how AI enhances decision accuracy, reduces time to decision, and improves operational efficiency. The analysis highlights the significant benefits that AI brings to industries such as healthcare, retail, financial services, manufacturing, and technology, where it is used to optimize processes, predict outcomes, and drive innovation. However, the paper also addresses the challenges associated with AI integration, including data quality issues, high implementation costs, and ethical concerns such as bias, transparency, and privacy. These challenges are examined through state machine diagrams that illustrate the decision-making process, the resolution of AI integration challenges, and the collaboration between AI systems and human decision-makers. The results indicate that while AI has a substantial positive impact on strategic decision-making, overcoming these challenges is crucial for maximizing its benefits. The paper concludes by discussing emerging trends in AI, such as Explainable AI and real-time decision-making, which are poised to further influence strategic management practices. Strategic recommendations are provided to guide organizations in effectively leveraging AI, ensuring that it complements human expertise, drives innovation, and is implemented ethically. This comprehensive analysis underscores the potential of AI to revolutionize strategic decision-making, positioning organizations for sustained success in a competitive and technology-driven market.